New and little-known Cheilostomata (Bryozoa, Gymnolaemata) from the NE Atlantic - Björn Berning (European Journal of Taxonomy, 2013)
Based on newly designated type material, four poorly known NE Atlantic cheilostome bryozoan species are redescribed and imaged: Cellaria harmelini d’Hondt from the northern Bay of Biscay, Hippomenella mucronelliformis (Waters) from Madeira, Myriapora bugei d’Hondt from the Azores, and Characodoma strangulatum, occurring from Mauritania to southern Portugal. Moreover, Notoplites saojorgensis sp. nov. from the Azores, formerly reported as Notoplites marsupiatus (Jullien), is newly described. The genus Hippomenella Canu & Bassler is transferred from the lepraliomorph family Escharinidae Tilbrook to the umbonulomorph family Romancheinidae Jullien.